Detection of Salmonella enterica serovar Enteritidis using real time PCR, immunocapture assay, PNA FISH and standard culture methods in different types of food samples - C. Almeida (2013)
Several methods for the rapid and specific detection of Salmonella in food samples have been described. Here, we compare 4 of those methods in terms of assay time, procedure complexity, detection limit, sensitivity, specificity and accuracy. Milk, eggs and mayonnaise samples were artificially contaminated with Salmonella enterica serovar Enteritidis cell concentrations ranging from 1 x 10(-2) to 1 x 10(2) CFU per 25 g or ml of food. Samples were then pre-enriched and analyzed by either: i) real-time PCR, using the iQ-Check Salmonella kit; ii) immunocapture, using the RapidChek SELECT Salmonella; iii) a peptide nucleic acid fluorescence in situ hybridization (PNA FISH) method and iv) the traditional bacteriological method ISO 6579:2002. All methods were able to detect Salmonella in the different types of food matrixes and presented a similar detection level of 1 CFU per 25 g or ml of food sample. The immunocapture and the PNA FISH methods proved to be very reliable, as their results were 100% in agreement with the ISO method. However, real-time PCR presented a significant number of false positives, which resulted in a specificity of 55.6% (CI 95%, 31.3-77.6) and an accuracy of 82.2% (CI 95%, 63.2-91.4) for this method. Sensitivity was 100% since no false negative results were observed. In conclusion, the implementation of these molecular techniques, mainly the immunocapture and PNA-FISH methods, provides a reliable and less time-consuming alternative for the detection of Salmonella spp. in food samples.